A study on the level of patriotism among students of polytechnic kuala terengganu in conjunction with the 65th independence day - Zainun Binti Salleh; Salmi Binti Mohd; Mohd Zuky Bin Hanafi (Indonesian Institute For Counseling, Education and Therapy, 2024)
Patriotism can be defined as the presence of love and affection for one's own country and the willingness to defend its sovereignty. This study was conducted to determine the level of patriotism among students at Politeknik Kuala Terengganu in conjunction with the 65th Independence Day celebration. A total of 80 students from two departments, the Department of Electrical Engineering and the Department of Information and Communication Technology, from semesters one to five for Session I: 2022/2023 were selected as respondents. This study combines both quantitative and qualitative methodologies. Quantitative data was obtained through questionnaires, while qualitative data was obtained through interviews. The findings of the study show that the level of patriotism among students at Politeknik Kuala Terengganu, based on the constructs of knowledge and attitude, is at a moderate level with a mean of 3.2. This indicates that the students have considerable knowledge about the country's history and independence and demonstrate good attitudes and activities in conjunction with the Independence Month. Interview findings from 75 students show that most students are aware of important national history. In conclusion, efforts to rekindle patriotic values need to be carried out continuously to further ignite the spirit of love for the country.